Ni2Mn-layered double oxide electrodes in organic electrolyte based supercapacitors - Hong, J; Chen, C; Siriviriyanun, A; Crivoi, D-G; Holdway, P; O'Hare, D; Buffet, J-C (Royal Society of Chemistry, 2021)
The development of future mobility (e.g. electric vehicles) requires supercapacitors with high voltage and high energy density. Conventional active carbon-based supercapacitors have almost reached their limit of energy density which is still far below the desired performance. Advanced materials, particularly metal hydroxides/oxides with tailored structure are promising supercapacitor electrodes to push the limit of energy density. To date, research has largely focused on evaluation of these materials in aqueous electrolyte, while this may enable high specific capacitance, it results in low working voltage window and poor cycle stability. Herein, we report the development of Ni2Mn-layered double oxides (Ni2Mn-LDOs) as mixed metal oxide-based supercapacitor electrodes for use in an organic electrolyte. Ni2Mn-LDO obtained by calcination of [Ni0.66Mn0.33(OH)2](CO3)0.175·nH2O at 400 °C produced the best performing Ni2Mn-LDOs with high working voltage of 2.5 V and a specific capacitance of 44 F g−1 (at 1 A g−1). We believe the performance of the Ni2Mn-LDOs is related to its unique porous structure, high surface area and the homogeneous mixed metal oxide network. Ni2Mn-LDO outperforms both the single metal oxides (NiO, MnO2) and the equivalent physical mixture of the two oxides. We propose this performance boost arises from synergy between NiO and MnOx due to a more effective homogeneous network of NiO/MnOx domains in the Ni2Mn-LDO. This work clearly shows the advantage of an LDO over the single component metal oxides as well as the physical mixture of mixed metal oxides and highlights the possibilities of development of further mixed metal oxides-based supercapacitors in organic electrolyte using LDH precursors.